OSS Design Patterns A Pattern Approach to the Design of Telecommunications Management Systems - Ashford, Colin; Gauthier, Pierre; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book advocates a pattern-based approach to the design of interfaces to Operations Support Systems (OSSs) to reduce the cost of delivering telecommunications management solutions. OSSs are the large servers that host the OSS applications that manage telecommunications services. Developing solutions to manage telecommunications services entails integrating the functionality of a number of OSS applications through their integration interfaces. Owing to the complexity, size, and distributed nature of telecommunications networks and services, application designers have necessarily turned to the latest software technologies to implement OSS applications. This has led to a proliferation of interface styles and underlying information models that makes systems integration both expensive and error prone. Rather than proposing yet another technology-specific interface specification and information model, this book makes the case for an agreement across the OSS community on a core set of technology-neutral OSS Design Patterns. The book details over a dozen OSS-specific design patterns$1 (Bmany based on proven distributed-systems patterns$1 (Bthat will help in the design of consistent interfaces to OSS applications. Each pattern is accompanied by examples of its implementation in two software technologies: Java Platform, Enterprise Edition and Java Message Service. OSS application designers will find that the book makes a compelling case for adopting these architectural and programming patterns to future-proof their designs. It is a valuable contribution to the growing ecosystem of best practices, common code, and proven designs for OSS applications and their interfaces.s
Part 1 - Overview of OSS Development: Introduction -- The Telecommunications-management Landscape -- Managing Telecommunications Networks -- Implementing OSS Client Systems -- Design Patterns -- Goals of the Book -- Part 2 - OSS Design Patterns: Introduction -- JEE as an OSS Implementation Architecture -- OSS Architectural Patterns -- Managed-entity-value Basic Patterns -- Managed-entity Selection Patterns -- Managed-entity Update Patterns -- Managed-Entity Life-Cycle Patterns -- Event-reporting Patterns -- Extension Patterns -- Distributed Location Patterns.
Keywords: Computer science; Computer communication systems; Software engineering; Electrical engineering; Computer Science; Computer Communication Networks; Communications Engineering, Networks; Information Systems Applications (incl. Internet).; Software Engineering; Electronic books